2005
DOI: 10.1103/physrevb.72.125406
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced complexity in a lithium monolayer:Ab initiocalculations

Abstract: Light alkali metals have usually been considered as simple metals due to their monovalency and high conductivity. In these metals ionic pseudopotentials are weak and the nearly free electron model (NFE) becomes quite accurate at normal conditions. However, very recent experiments have shown that at high pressures their electronic properties deviate radically from the NFE model and even become unexpected good superconductors. In this work we present ab initio calculations to analyze the deviation from simplicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
2
34
1
Order By: Relevance
“…In fact, as a consequence of the induced s-p orbital mixing, 1 pressure makes them depart from their simplicity at ambient conditions to become metals with rather complex behavior. 2 Not only superconductivity arises under pressure in lithium with a large T c , 3,4 but, even more strikingly, both lithium and sodium become semiconductors when further compressed, 5,6 confirming the predictions made by Neaton and Ashcroft. 7,8 Moreover, contradicting common sense, the melting curve of the alkalies shows a negative slope of the melting temperature as a function of pressure in a wide pressure range, [9][10][11][12][13] principally, due to the softening of a transverse phonon mode induced by compression.…”
Section: Introductionsupporting
confidence: 72%
“…In fact, as a consequence of the induced s-p orbital mixing, 1 pressure makes them depart from their simplicity at ambient conditions to become metals with rather complex behavior. 2 Not only superconductivity arises under pressure in lithium with a large T c , 3,4 but, even more strikingly, both lithium and sodium become semiconductors when further compressed, 5,6 confirming the predictions made by Neaton and Ashcroft. 7,8 Moreover, contradicting common sense, the melting curve of the alkalies shows a negative slope of the melting temperature as a function of pressure in a wide pressure range, [9][10][11][12][13] principally, due to the softening of a transverse phonon mode induced by compression.…”
Section: Introductionsupporting
confidence: 72%
“…However, new theoretical and experimental results have shown that under pressure light alkalies depart radically from this simple behavior, as phase transitions to complex and low-coordinated structures emerge. [2][3][4][5] According to a recent x-ray analysis 3) lithium undergoes a bcc to fcc transition at 7.5 GPa, followed by a fcc to hR1 at 39 GPa and a hR1 to cI16 at around 40 GPa. On the other hand, despite experiments looking for superconductivity in lithium at equilibrium have failed, 8) it has been observed to superconduct at 20 K when pressure rises to 40 GPa.…”
mentioning
confidence: 99%
“…Therefore, we have two types of carriers at the Fermi energy, a fact which plays a fundamental role in the pressure induced properties of the electronic collective excitations, as will be explained bellow. It is noteworthy that the Fermi line of the ML also suffers significant deviations with increasing electronic density [10], as it is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 72%
“…In addition, extending our conclusions to the bulk will also give another perspective to understand the physical origin under the experimentally observed features in compressed lithium. Previous ab initio analysis of the structural and electronic properties of a lithium ML [9,10] reveal important modifications in both its band structure and Fermi line, which will also lead to significant modifications on its dynamical response function, up to now just studied at equilibrium [11]. In this article we perform calculations of the dynamical response function of a lithium ML at different pressures, analyzing its evolution with increasing electronic density.…”
Section: Introductionmentioning
confidence: 99%